Brand Differentiation and Digital Marketplace Innovation under Trademark Law: Insights from Indonesia’s Law No. 20 of 2016 - Dewi Sulastri; Neng Yani Nurhayani (FEBI IAIN Langsa, 2026)
This study examines the relationship between brand differentiation strategies, technological innovation in digital marketplaces, and trademark protection under Indonesia’s Law No. 20 of 2016. Using a qualitative empirical–juridical approach, the research draws on semi-structured interviews with intellectual property officials, business actors, and marketplace stakeholders, complemented by document analysis and case studies. The findings indicate that global market competition and digitalisation encourage firms to strengthen brand differentiation through digital ecosystems, data-driven marketing, and platform technologies such as AI and blockchain. However, regulatory fragmentation, cross-border enforcement challenges, and limited intellectual property awareness among MSMEs hinder effective trademark protection. The study contributes to the literature by highlighting the emerging implications of immersive technologies (VR, AR, XR, and metaverse environments) for trademark protection and proposing an adaptive regulatory framework that integrates state regulation, platform governance, and business innovation.